Assessment of Physicochemical Parameters in Two Winegrapes Varieties after Foliar Application of ZnSO4 and ZnO - Daccak, Diana (2023)
The authors thank Engenier Luís Silva (Adega Cooperativa de Palmela-Casa Agrícola Nunes Oliveira da Silva Lda) for technical assistance to project PDR2020-101-030727– for the financial support. Associate Laboratory TERRA (LA/P/0092/2020). This work was further supported in part by the research center Grant N°. UID/FIS/04559/2020 to LIBPhys-UNL, from the FCT/MCTES/PIDDAC and by the project PDR2020-101-030727. Publisher Copyright: © 2023 by the authors.